The footloose entrepreneur model with a finite number of equidistant regions - Gaspar, José M. (2021)
We study the Footloose Entrepreneur model with a finite number of equidistant regions, focusing on the analysis of stability of agglomeration, total dispersion, and boundary dispersion. As the number of regions increases, there is more tendency for agglomeration and less tendency for dispersion. As it tends to infinity, agglomeration always becomes stable while dispersion always becomes unstable. These results are robust to any composition of the global workforce and its dependence on the number of regions. Numerical evidence suggests that boundary dispersion is never stable. We introduce exogenous regional heterogeneity and obtain a general condition for stability of agglomeration.